2012
DOI: 10.1007/s00134-012-2595-z
|View full text |Cite
|
Sign up to set email alerts
|

Ordering CT pulmonary angiography to exclude pulmonary embolism: defense versus evidence in the emergency room

Abstract: Purpose: To identify reasons for ordering computed tomography pulmonary angiography (CTPA), to identify the frequency of reasons for CTPA reflecting defensive behavior and evidence-based behavior, and to identify the impact of defensive medicine and of training about diagnosing pulmonary embolism (PE) on positive results of CTPA. Methods: Physicians in the emergency department of a tertiary care hospital completed a questionnaire before CTPA after being trained about diagnosing PE and completing questionnaires… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 23 publications
1
40
0
Order By: Relevance
“…This trend has also been observed in Europe. In Switzerland, such defensive behaviour is frequent and is consistent with a low prevalence of positive CTPA findings [28]. The increased incidence of PE has been found to be strongly correlated with the increased use of CTPA [16].…”
mentioning
confidence: 77%
“…This trend has also been observed in Europe. In Switzerland, such defensive behaviour is frequent and is consistent with a low prevalence of positive CTPA findings [28]. The increased incidence of PE has been found to be strongly correlated with the increased use of CTPA [16].…”
mentioning
confidence: 77%
“…A recent survey of physicians ordering CTPA scans for diagnosing PE found that defensive behavior (e.g., fear of missing PE, threat of malpractice litigation) was a factor in nearly three of five scans. These factors kept pace with other evidence‐based medicine factors for driving the post‐imaging clinician decision making 30. A 2005 survey of Pennsylvania ED physicians found that 63% ordered radiologic tests that were not indicated, while 93% of physicians, in general, practice defensive medicine 31.…”
Section: Discussionmentioning
confidence: 99%
“…A Massachusetts‐based survey revealed that 23% of all types of CTs were ordered for defensive reasons 32. While the role of defensive medicine in driving up healthcare costs is controversial, these behaviors are estimated to cost the US healthcare system up to $45 billion to $100 billion annually and are thought to account for 5% to 25% of all US medical care costs 30. While behavior modification in dealing with physician risk aversion has a definite role to play in using imaging resources judiciously and efficiently, this also highlights an unmet need that SPECT/CT can potentially fill as a result of its superior diagnostic accuracy and efficiency, which reduces the overall cost burden.…”
Section: Discussionmentioning
confidence: 99%
“…It appears that, even with risk prediction tools, only a small minority (10-20%) of patients who have a CT pulmonary angiogram (CTPA) have a PE [13]. As a profession, we are ordering CTPAs out of paranoia [14] and ignoring the radiation dose required, which is equivalent Figure 1Pathophysiology of pulmonary embolus. Copied with permission from [50].…”
Section: Epidemiology Of Acute Pulmonary Embolism Due To Venous Thrommentioning
confidence: 99%